Adequate Conscious Life and Age-Related Need: F.M. Kamm's Approach to Patient Selection - Waring, Duff (Bioethics, 2004)
Kamm's approach to patient selection qualifies the notion that fairness makes need for scarce, transplantable organs inversely proportional to age. She defines need as how much adequate conscious life a person will have had before death. Length of adequate conscious life correlates highly with age. If so, then younger persons are usually needier than older ones. Since Kamm allows for past periods of non-adequate conscious life, I argue that this correlation may be neither as close, nor as easy to apply, as she wants it to be. Fairness should require assessment of experiential content in determining how long one's life has been adequately conscious. I argue that such assessments involve some of the goods of experience and quality of life judgements that Kamm thinks a reliance on adequate conscious life will avoid.